Development and Expert Review of iZakat Kedah Mobile Application - Omar, Azizah Che; Aziz, Nurulnadwan; Abd Muin, Mohd Adib; Annamalai, Subashini A/P; Mahmad, Muhamad Amar (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Zakat is a mandatory practice in Islam. The purpose of zakat is to help the society, share the endless boons of Allah and assists the unfortunate people to have a better quality of life. The concept of Zakat is to purify the Muslim wealth and soul. Calculation of Zakat is based on the total savings of a Muslim during one lunar (Islamic) year. Even though, paying Zakat is compulsory for all Muslims however, the knowledge of zakat and the calculation of zakat is still insufficiently explored by the Muslims themselves. Based on the initial study that has been carried out, most of the Muslims still blur and confuse in understanding the concept of zakat and the calculation of zakat. Therefore, iZakat Kedah mobile application has been developed to provides understanding of the zakat income and the calculation of zakat. Thus, this paper focuses on the development of iZakat Kedah mobile application which has been carried out through comparative analysis study and the evaluation of the proposed application through expert review method. Findings of the study indicates that most of the experts agreed that the iZakat Kedah mobile application provides useful knowledge in terms of zakat information and zakat calculation to the public particularly for Muslims.